THE EFFECT OF BRAND IMAGE AND PRODUCT QUALITY ON CONSUMER PURCHASE DECISIONS ON 'SKINCARE INE' COSMETIC PRODUCTS AT THE CIKARANG SKIN CENTER MEDIATED BY WORD OF MOUTH - Indra Setiawan; Dede Mulyana; Agus Prianto; Melati Desi; Retno Purwani Setyaningrum (Jurnal Ekonomi, 2023)
In the current era of globalization, competition in the cosmetics business is getting tougher and requires the right marketing strategy to attract consumers. One of the factors that can influence consumer decisions in buying cosmetic products is brand image and product quality. The purpose of this study was to find out whether the brand image and product quality variables affect the decision to buy INE skincare products, the method used in this study uses a scientific approach by collecting and analyzing quantitative data, namely data that can be measured using numbers and statistics, with conducting research on a portion of the population in Cikarang and its surroundings, it is hoped that the results of this study are able to describe the population concerned. The sample of this research is 72 respondents and the data analysis method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The results of this respondent's data processing show that brand image (X1) has no significant effect with a result of 0.829 > 0.05, then the influence of product quality (X2) has a significant effect with a result of 0.000 <0.05, then the influence of word of mouth promotion (Z) has a significant effect with a result of 0.000 <0.05, on the decision to buy (Y) for INE skincare products.